Researches of emission spectra of liquid-phase objects during gas discharge visualization - Білинський, Йосип Йосипович; Павлюк, Олександр Анатолійович; Юкиш, Сергій Васильович (Technology audit and production reserves, 2014)
Ukraine faces the issue of express control of impurities in water or in liquid - phase object, in particular – the mineralization in the systems for central fresh water supply. The existing methods for the analysis of liquid phase objects are based on chemical analysis, photo and colorimetry, gravimetry, spectroscopy, conductometry. Methods, based on measuring the electric resistance are usually used for the determination of the general mineralization. This, however, does not allow to determine the small concentration values of general mineralization with sufficient accuracy. Therefore, there had been suggested the method for the determination of the small concentration of the general liquid phase object mineralization by emissions spectrum registration during gas discharge visualization which allows to improve the accuracy in determination of the general mineralization with short-term measurements and cheap equipment. In accordance with the suggested method there had been developed the experimental unit, on which there had been conducted the series of experiments with water-soluble salts NaCl, MgSO4, KCl, CaCl2, FeSO4; there had been received their emissions spectrums. There had been determined that for Na1+, Cl1-, Mg2+, Fe3+, Ca2+ ions there is observed the higher spectral lines for wavelengths that are close to wavelengths of spectrum lines of those elements. There had been proved the possibility for the determination of availability of several salts in one liquid phase object. The obtained results prove the possibility of using the suggested method for the determination of the general mineralization. It enables to create in future the automated system for controlling over the minaralisation for the system of fresh water supply.